SOLVING SYSTEM OF SECOND ORDER BOUNDARY VALUE PROBLEMS BY NUMEROV TYPE METHOD - Pandey, Pramod Kumar (Journal of the sciences and arts, 2015)
The aim of this paper is to describe an efficient numerical method for solving system of two-point boundary value problems subject to the Dirichelet boundary conditions. We present the construction of Numerov type method by assuming extra continuity condition on the solution. The order of the propose method is quadratic. This propose method is suitable for solving an obstacle problems. We have considered an obstacle problem and solved by the propose method to illustrate the efficiency and the accuracy. Results are compared with the other methods.